KOMPOSISI BOTANI HIJAUAN ALAMI DI AREAL PERKEBUNAN KELAPA DALAM SEBAGAI PAKAN TERNAK RUMINANSIA DI KECAMATAN TANIWEL KABUPATEN SERAM BAGIAN BARAT - Eoh, Marna; Rehatta, Lea Marylin (Program Studi Pendidikan Biologi FKIP Unpatti, 2024)
ackground: The need for and provision of forage is achieved by considering the continuous provision of forage in both quantity and quality. One of the efforts to develop animal husbandry that can be carried out is to utilize forage for livestock in deep coconut plantations. This research aims to determine the botanical composition of natural forage in coconut plantation areas as feed for ruminants in Taniwel District, West Seram Regency. Method s : This research uses a purposive sampling method. The data used in this research is based on secondary data and primary data. Results : The research results showed that the botanical composition results were 63.18% grass, 26.30% weeds and 10.52% legumes. Co nclusion: Based on the research results, it is necessary to eradicate pest plants (weeds) for forage and plant superior forage to increase the need for feed for ruminant livestock. The availability of forage can still meet the need for animal feed in Taniw el District, West Seram Regency